Economic Determinants of the Relation between Earnings Changes and Stock Returns - Ball, Ray; Kothari, S. P.; Watts, Ross L. (The Accounting Review, 1993)
[In competitive product markets, product prices and thus firms' revenues incorporate the cost of equity capital. In a competitive capital market, the cost of equity capital (the expected return on equity) increases with the risk of firms' investments. Because accounting earnings are calculated without deducting the cost of equity capital, they are expected to be an increasing function of firms' investment risks. This simple competitive equilibrium analysis predicts a positive relation between changes in investment risk and expected earnings. The presence of corporate debt complicates the analysis because leverage effects seem likely to affect the relation between changes in investment risk and expected earnings. Using annual earnings and return data from 1950 to 1988, we document a statistically significant positive association between changes in equities' relative risks and in earnings. However, on average, only a small proportion of changes in earnings can be attributed to changes in risk. A much larger proportion is attributable to changes in economic rents (windfall gains and losses). The observed positive association between changes in earnings and changes in equities' risks suggests that leverage effects do not fully offset the effect of changes in investment risks. This association is robust with respect to subperiod analysis, alternative specifications of the earnings change variable, alternative data-availability requirements, and the number of portfolios formed.]